Psychological and family factors that influence the occurance of juvenile delinquency - Slavković, Ana R; Slavković, Vukan R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
In this paper, the aggressiveness and delinquent behavior of adolescents is placed in the context of developmental turbulence that can be temporary. In the case of a young person who violates legal norms, there may be potential for a healthy personality development, and antisocial behavior can be greatly influenced by the developmental characteristics of adolescence: internal conflicts, reactivation of early developmental crises, intrapsychic difficulties related to separation from parents, identity crisis and forming the so-called negative identity. This paper explores the influence of the early child development on the formation of tendencies towards aggressive behavior, as well as the influence of family factors on the occurrence of juvenile delinquency. Finally, the author concludes that in forming a healthy personality with prosocial values, the proper upbringing in the family is the most important. If the family has a healthy foundation for personality development, sources of socialization and other socialization agents can hardly disrupt the proper development of an adolescent, except when it comes to the inherent tendency towards the formation of psychopathic personality traits. Otherwise, the adolescent is very susceptible to accepting inadequate patterns and blindly following the peer group, where he tries to obtain the support and intimacy that he has not received in the family. The peer group can sometimes impose antisocial values and behaviors as desirable ones.